Symptomatic subsegmental versus more central pulmonary embolism: Clinical outcomes during anticoagulation - Carmen Fernández‐Capitán; Ana Rodriguez Cobo; David Jiménez; Olga Madridano; Maurizio Ciammaichella; Esther Usandizaga; Remedios Otero; Pierpaolo Di Micco; Farès Moustafa; Manuel Monreal; The RIETE Investigators (Research and Practice in Thrombosis and Haemostasis, 2021)
Abstract Background The optimal therapy of patients with acute subsegmental pulmonary embolism (PE) is controversial. Methods We used the RIETE (Registro Informatizado Enfermedad TromboEmbólica) database to compare the rate of symptomatic PE recurrences during anticoagulation in patients with subsegmental, segmental, or more central PEs. Results Among 15 963 patients with a first episode of symptomatic PE, 834 (5.2%) had subsegmental PE, 3797 (24%) segmental, and 11 332 (71%) more central PE. Most patients in all subgroups received initial therapy with low‐molecular‐weight heparin, and then most switched to vitamin K antagonists. Median duration of therapy was 179, 185, and 204 days, respectively. During anticoagulation, 183 patients developed PE recurrences, 131 developed deep vein thrombosis (DVT), 543 bled, and 1718 died (fatal PE, 135). The rate of PE recurrences was twofold higher in patients with subsegmental PE than in those with segmental (hazard ratio [HR], 2.13; 95% confidence interval [CI], 1.16‐3.85) or more central PE (HR, 1.89; 95% CI, 1.12‐3.13). On multivariable analysis, patients with subsegmental PE had a higher risk for PE recurrences than those with central PE (adjusted HR, 1.75; 95% CI, 1.02‐3.03). After stratifying patients with subsegmental PE according to ultrasound imaging in the lower limbs, the rate of PE recurrences was similar in patients with DVT, in patients without DVT, and in those with no ultrasound imaging. Conclusions Our study reveals that the risk for PE recurrences in patients with segmental PE is not lower than in those with more central PE, thus suggesting that the risk of PE recurrences is not influenced by the anatomic location of PE.